(untitled) (Revista Tempo e Argumento, 2019)
This article aims to describe and analyze how the debate about labor relations in the field of childhood, adolescence, and youth was framed during the construction of the Convention on the Rights of the Child by member countries of the United Nations (UN) and non-governmental organizations (NGOs) between 1978 and 1989. It also seeks to provide information on the presence of the legal discourse contained in this international law agreement in the Brazilian legislation for children, teenagers, and young people enacted in the country in the year 1990. Keywords: History; Childhood; Youth; Rights; Labor Relations.